Biophysico‐functional compatibility of Seoul National University (SNU) miniature pig cornea as xenocorneal graft for the use of human clinical trial. (11th May 2016) - Kim, Dong Hyun; Kim, Jaeyoung; Jeong, Hyun Jeong; Lee, Hyun Ju; Kim, Mee Kum; Wee, Won Ryang
Abstract: Background: Xenocorneal transplantation is one of the solutions for shortage of donor cornea, and remarkable advances have been made in pig‐to‐rhesus studies from the immunological perspective. Most successful preclinical trials have been carried out with corneas of the Seoul National University (SNU) miniature pig (SNU pig, genetically unmodified) as donor tissues; however, there has been no biophysico‐functional evaluation of the SNU pig cornea as a substitute for human cornea. The purpose of this study was to investigate the biophysical and functional compatibility of SNU pig cornea for use in human clinical trials. Methods: Ninety‐three eyeballs obtained from 51 SNU pigs were used to evaluate the physical properties and changes in porcine corneal endothelial cells (PCECs) depending on preservation time and storage condition before surgery, proliferative and functional characteristics of PCECs, and the microbiologic safety of porcine cornea. Corneal diameters and curvatures, axial length, anterior chamber depth, and central corneal thickness were measured and compared with previously reported human data. Corneal endothelial cell density (ECD) was serially measured with a confocal microscope during 7 days of preservation in the same storage solution used for human corneas. Corneal endothelial cell proliferation and immunofluorescence staining of Na‐ and K‐dependent ATPase in PCECs were evaluated after 7 days of preservation. The corneoscleral rims of SNU pigs were cultured for gram‐positive bacteria, gram‐negative bacteria, and fungi to evaluate their microbiological safety. Results: Corneal diameter and thickness in SNU pigs was larger than human and corneal curvature was flatter; however, they were within surgically operable ranges. Mean ECD (day 0) and ECD loss after 7 days of preservation were 2625 ± 81 cells/mm 2 and 7.60 ± 1.53%, respectively, which is comparable to human ECD and ECD loss in the same conditions. The ECD of SNU pigs was inversely decreased with aging ( R 2 = 0.4034, P = 0.001), and the estimated ages of pigs whose mean ECD would be more than 2500 and 2200 cells/mm 2 or more were 48 and 72 months or less, respectively. Mean doubling time of the endothelial cells was 52 to 96 h depending on the method used. The Na‐ and K‐dependent ATPase pump in SNU pig cornea was well maintained for 7 days. No cultured microorganisms were found upon using the modified European Eye Bank Association protocol, which included additional antiseptic management during the enucleation procedure. Conclusions: In conclusion, SNU pig cornea is feasible for xenocorneal transplantation using the same preservation protocol as human with respect to biophysical and functional properties and can be stored for up to 7 days for transplantation in human clinical trials. An age limitation of donor pigs may be required for qualified corneal products to be used in human trials.